Modulation of Monocyte-Driven Myositis in Alphavirus Infection Reveals a Role for CX(3)CR1(+) Macrophages in Tissue Repair - Zaid, Ali (mBio, 2020)
Arthritogenic alphaviruses such as Ross River and Chikungunya viruses cause debilitating muscle and joint pain and pose significant challenges in the light of recent outbreaks. How host immune responses are orchestrated after alphaviral infections and lead to musculoskeletal inflammation remains poorly understood. Here, we show that myositis induced by Ross River virus (RRV) infection is driven by CD11b(hi) Ly6C(hi) inflammatory monocytes and followed by the establishment of a CD11b(hi) Ly6C(lo) CX(3)CR1(+) macrophage population in the muscle upon recovery. Selective modulation of CD11b(hi) Ly6C(hi) monocyte migration to infected muscle using immune-modifying microparticles (IMP) reduced disease score, tissue damage, and inflammation and promoted the accumulation of CX(3)CR1(+) macrophages, enhancing recovery and resolution. Here, we detail the role of immune pathology, describing a poorly characterized muscle macrophage subset as part of the dynamics of alphavirus-induced myositis and tissue recovery and identify IMP as an effective immunomodulatory approach. Given the lack of specific treatments available for alphavirus-induced pathologies, this study highlights a therapeutic potential for simple immune modulation by IMP in infected individuals in the event of large alphavirus outbreaks.